Analisis Pengaruh Inovasi, Kualitas, Harga, Dan Citra Merek Terhadap Keputusan Pembelian Produk Sibaya di PT Gama Inovasi Berdikari - Ergilia nur cholifah; Joumil Aidil SZS (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Purchasing decisions are the thoughts that arise in an individual after comparing the perceptions of several components of a product with their expectations. The purpose of this research is to determine the implementation of Total Quality Management in enhancing the purchasing decisions of SIBAYA products at PT. Gama Inovasi Berdikari. This study involved 30 respondents, specifically individuals who visited the PT. Gama Inovasi Berdikari booth and were interested in SIBAYA products. The data collection method employed was the use of a questionnaire, and the gathered data were processed using SPSS software. The data analysis results revealed a significant influence of Total Quality Management (TQM) on purchasing decisions, contributing to a 79.2% impact on the purchasing decisions of SIBAYA products. The multiple linear regression equation obtained is Y = -2.632 + 0.218X1 + 0.005X2 0.442X3 + 0.463X4.